Ее последний герой: роман / Мария Метлицкая - Метлицкая Мария (Женские судьбы, 2019)
Экземпляры: аб. ЦБ (20200618) / Инвентарный номер: 9352 / Цена: / Сис.шифр: 84(2Pос=Рус)6 / Авт.знак: М 54 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6-44